Pre-mRNA processing factor 19 functions in DNA damage repair and radioresistance by modulating cyclin D1 in hepatocellular carcinoma - Xiang-Nan Yu; Guang-Cong Zhang; Hai-Ning Liu; Jin-Min Zhu; Tao-Tao Liu; Guang-Qi Song; Ling Dong; Jie Yin; Xi-Zhong Shen (Elsevier, 2022)
Pre-mRNA processing factor 19 (PRP19) is elevated in hepatocellular carcinoma (HCC); however, little is known about its function in DNA damage repair in HCC. In this study, analysis of The Cancer Genome Atlas data and our tumor models after ionizing radiation (IR) treatment indicated that increased expression of PRP19 was positively correlated with DNA damage repair. Gain of PRP19 expression induced by plasmids resulted in decreases in apoptosis and double-strand breaks (DSBs), and an increase in cell survival after IR. Loss of PRP19 expression induced by small interfering RNAs resulted in the accumulation of apoptosis and DSBs, and a decrease in cell survival. Mechanistically, the effect of PRP19 on DNA damage repair was mediated by the modulation of cyclin D1 expression in HCC. PRP19 controlled the translation of cyclin D1 by modulating eukaryotic initiation factor 4E. PRP19 affected the DNA damage repair ability of cyclin D1 by interacting with the WD40 domain. The combination of PRP19 and cyclin D1 was more valuable than each single marker for predicting the prognosis of patients. Taken together, the present results demonstrate that PRP19 promotes DNA damage repair by modulating cyclin D1 expression and function, thereby contributing to the radioresistance in HCC.